Molecular mechanisms of underlying genetic factors and associated mutations for drug resistance in Mycobacterium tuberculosis. Issue 1 (1st January 2020) - Swain, Shasank S.; Sharma, Divakar; Hussain, Tahziba; Pati, Sanghamitra
ABSTRACT: Nowadays, drug-resistant tuberculosis (DR-TB) and co-infected tuberculosis (CI-TB) strains are the leading cause for the enhancement of long-term morbidity and unpredicted mortality rates from this ghoulish acid fast-bacterium infection, globally. Unfortunately, the lack of/ample lethargic towards the development of compelling anti-TB regimens with a large-scale prevalence rate is a great challenge towards control of the pandemic situation. Indeed, the recent improvement in genomic studies for early diagnosis and understanding the mechanisms of drug resistance, as well as the identification of newer drug targets is quite remarkable and promising. Mainly, identification of such genetic factors, chromosomal mutations and associated pathways gives new ray of hope in current anti-TB drug discovery. This focused review provides molecular insights into the updated drug resistance mechanisms with encoded bacilli genetic factors as a novel target and potential source of development with screened-out newer anti-TB agents towards the control of MDR-TB soon.